The Association of Body Temperature with Longevity: Insights from Historical Cohorts - Chmielewski, Piotr Paweł; Chmielowiec, Krzysztof (Anthropological Review, 2025)
Effective thermoregulation is crucial for maintaining homeostasis. Previous research has suggested a link between lower steady-state body temperature and longevity, particularly in physically healthy, nonobese older adults. However, the exact mechanisms behind this relationship remain unclear. Despite the physiological insights gained from studies on body temperature, limited attention has been given to its potential role as a biomarker of longevity in physically healthy older populations. This study aimed to evaluate the relationship between body temperature and longevity using historical data from two cohorts. The longitudinal cohort consisted of 142 individuals, followed for 25 years beginning at age 45, while the cross-sectional cohort included 204 individuals stratified into four lifespan categories. To examine agerelated trends in body temperature, Page’s test was employed, and ordinal regression was used. The analysis revealed a significant decrease in body temperature in women with age, while men showed no significant change. The cross-sectional analysis indicated a trend toward lower body temperatures in individuals with longer lifespans. Lower body temperature may reflect a reduced metabolic rate, thereby mitigating oxidative stress and molecular damage, both of which are known to drive aging and limit lifespan. Furthermore, lower body temperatures may signal a favorable inflammatory profile, which could translate into slower aging and increased survival. However, the observed sex-specific differences in thermoregulatory patterns raise important questions about the role of hormonal influences, such as estrogen levels. Overall, these findings suggest that lower lifetime steady-state body temperature may be a biomarker of healthy aging and longevity, warranting further exploration of its mechanistic underpinnings.